KARAKTER IBU TIRI SELALU JAHAT ? (Studi Perbandingan Cerita Rakyat Indonesia) - Aurelius Ratu (Institut Teknologi Sepuluh Nopember, 2017)
The story of the stepmother in almost all cultures often describes her as evil, ambitious, and cruel. This paper presents a comparative study of two Indonesian folklore that presents the theme of stepmother. Through a structural and sociological approach, it is found that the storyline is not much different from the folktale of the stepmother in general. What distinguishes it is the heroic or supernatural part of it gets less emphasis even though it still remain exists. Apparently, such stories need special attention (revision), especially for the formation of a stepmother image in the midst of society so that negative stigma does not adversely affect the child's life